The Development of Women’s Movements and Their Role in The Emergence of Women’s Journalism in Algeria. - guenfoud, ridha (Journal of Social Sciences and Humanities, 2024)
Our research paper aims to shed light on the reality of feminist movements and their role in the emergence and development of women's journalism in Algeria, where the emergence of the term feminism was accompanied by the liberation of women, specifically when the signs and maturity of women themselves began and an attempt to remove the injustice that falls on them, at a time when voices began calling for gender equality and freedom, fighting all forms of racial discrimination, and defending their rights, and the Western-born movement is concerned with women's issues in general, and it is one of the trends of what is known as postmodernism, where these feminist militant associations harnessed the media, which is an authority and tools to express empowerment, influence societies to realize and pass on their ideologies Specialized Women's journalism was one of its tools and strategies, as it played a large and supportive role in serving the programs and goals of women's militant associations and organizations, shedding light on the most important issues and intellectual and social aspects of women and defending their rights . We have relied on the historical approach, which is based on the collection of information, historical facts and archives during a period of time when they witnessed the emergence of newspapers and magazines speaking on behalf of feminist movements in Algeria, from primary and secondary sources, analyzing and criticizing them